2011
DOI: 10.1007/s11524-011-9566-5
|View full text |Cite
|
Sign up to set email alerts
|

History of Arrest and Associated Factors among Men Who Have Sex with Men

Abstract: Incarceration has been proposed to be a driving factor in the disproportionate impact of HIV in African-American communities. However, few data have been reported on disparities in criminal justice involvement by race among men who have sex with men (MSM). To describe history of arrest and associated factors among, we used data from CDC's National HIV Behavioral Surveillance system. Respondents were recruited by time-space sampling in venues frequented by MSM in 15 US cities from 2003 to 2005. Data on recent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 37 publications
3
35
0
Order By: Relevance
“…14,15 Among MSM in the National HIV Behavioral Surveillance System (NHBS), 6.8 % had been arrested in the past 12 months. 16 One study has suggested that male youth who report same-sex attraction or a same-sex relationship are more likely to be stopped by the police as compared to heterosexuals. 17 Arrest has been associated with HIV risk behaviors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Among MSM in the National HIV Behavioral Surveillance System (NHBS), 6.8 % had been arrested in the past 12 months. 16 One study has suggested that male youth who report same-sex attraction or a same-sex relationship are more likely to be stopped by the police as compared to heterosexuals. 17 Arrest has been associated with HIV risk behaviors.…”
mentioning
confidence: 99%
“…19 Among MSM in the NHBS, arrest in the past 12 months was significantly associated with a higher odds of non-injection and injection drug use, unprotected anal sex (UAS), exchanging sex, and six or more male sex partners in the last 12 months. 16 Additionally, Fisher et al 14 reported that MSM with a history of arrest were more likely to have had an STI and have paid or been paid for sex, and Kurtz et al 15 found substance-using MSM in Miami were more likely to experience high levels of sex sensation seeking.…”
mentioning
confidence: 99%
“…Syndemic Health Disparities among African American/Black MSM A brief review of the literature on African American/Black MSM demonstrates the presence of health and social disparities related to substance use (Harawa et al 2008;Mimiaga et al 2010;Hatfield et al, 2009;Tobin et al 2011), HIV transmission or infection risk (Millett et al 2006;Millett et al 2007;Oster et al 2011), arrest history (Lim et al 2011), inadequate coping skills and social support (Kraft et al 2000;Shoptaw et al 2009), and social or cultural barriers Saleh et al 2011;Garofalo et al 2010;Harawa et al 2008;Haile et al 2011), among others. Whereas, one apparent article in the literature has addressed these concerns from a syndemic perspective (Dyer et al 2012) it was unable to address any larger socio-cultural or structural factors that contribute the specific health disparities among this population.…”
Section: Syndemic Theory and Msmmentioning
confidence: 99%
“…The poverty rate among African Americans is highest among all racial/ethnic groups, and it is nearly double the national poverty rate (DeNavas-Walt et al 2012). Overall, African-Americans are more likely to be homeless, to be incarcerated, and to experience inequitable access to social, educational, or material resources (Lim et al 2011, Bassuk et al 1997Susser et al 1993;Brondolo et al 2009). As cited in Williams et al (2010), the African American/Black population in the U.S. accounts 48% of individuals living with HIV/AIDS.…”
Section: Structural Inequalities Among African American/black Msmmentioning
confidence: 99%
See 1 more Smart Citation